1997
DOI: 10.1080/014461997373123
|View full text |Cite
|
Sign up to set email alerts
|

Communication and governance in the building process

Abstract: Through a proposed interpretative framework the relationship between forms of transactional governance and type of information processing and communication media is analysed. Building projects are successfully completed through the development of federative mechanisms, such as cooperation, informal roles and rules, that complement and circumvent the hierarchical and formal provisions of standard contracts. At present there is a dislocation between the pattern of roles and rules advocated by standard contracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 13 publications
0
63
0
Order By: Relevance
“…Empirical evidence from a previous study suggests that ineffective communication among stakeholders is a significant factor responsible for poor performance of construction projects (Atkinson, 2002;Ng et al, 2004). In a similar vein, Meng Pietroforte (1997) proposed a framework for analysing the contractual process and information requirement in the building process. It was revealed that differences in the perception of project team members and nature of information affects information flow.…”
Section: Significance Limitations and Areas For Further Researchmentioning
confidence: 99%
“…Empirical evidence from a previous study suggests that ineffective communication among stakeholders is a significant factor responsible for poor performance of construction projects (Atkinson, 2002;Ng et al, 2004). In a similar vein, Meng Pietroforte (1997) proposed a framework for analysing the contractual process and information requirement in the building process. It was revealed that differences in the perception of project team members and nature of information affects information flow.…”
Section: Significance Limitations and Areas For Further Researchmentioning
confidence: 99%
“…As the design process has a large number of participants and a high degree of interdependence of building design, the demand for informal contact is increased ( Pietroforte, 1997 ). The uncertain nature of refurbishment projects requires an approach that is more fl exible.…”
Section: Direct Informal Contactmentioning
confidence: 99%
“…Conflicts of interests increase the importance of information as a source of power in negotiations and make people more secretive with it. Parties can manipulate information in their own favour (Loosemore, 1999;Pietroforte, 1997). The result can be a lack of open communication or sending unclear or uninformative messages.…”
Section: Communication In Constructionmentioning
confidence: 99%
“…In construction projects, efficient communication is often made difficult by the different frames of reference of its participants (Pietroforte, 1997). The different frames of reference are the result of the different professional background of the parties involved (Cheng et al, 2001;Moore and Dainty, 2001).…”
Section: Communication In Constructionmentioning
confidence: 99%
See 1 more Smart Citation